Treatment of Yellow Phosphorus Slag and Reuse of It as an Absorbent of Chromium (VI) Ions and Methylene Blue - Van Hai Nguyen; Van Chien Nguyen; Thuy Chinh Nguyen; Do Mai Trang Tran; Thi Thu Trang Nguyen; Quoc Trung Vu; Duy Trinh Nguyen; Hoang Thai (Journal of Chemistry)
Yellow phosphorus is used widely in the world for production of phosphoric acid, various phosphates, flame retardant, detergent, water treatment, metal surface treatment, etc. After the production of yellow phosphorus, a large amount of phosphorus sludge is discharged to environment, causing environment pollution. This work focused on treatment of yellow phosphorus slag (YPS) and application of it as an absorbent for chromium (VI) ion and methylene blue. The YPS was first washed with water to remove phosphoferrite (FeP) and impurities and then being milled and transferred to a float sorting system to obtain YPS particles. The characteristics of YPS particles were determined by inductively coupled plasma-mass-spectrometry (ICP-MS), energy-dispersive X-ray spectroscopy (EDX), infrared spectroscopy (IR), scanning electron microscopy (SEM), X-ray diffraction (XRD), zeta potential, and nitrogen adsorption methods. The YPS particles were retreated with NaOH, HNO3, and EDTA solutions to evaluate the influence of these agents on metal ion and organic compound adsorption ability by YPS. The adsorption parameters of chromium (VI) ion and methylene blue (MB) by treated YPS particles were recognized by the ultraviolet-visible (UV-Vis) spectrometer. The effects of temperature, pH solution, and initial concentration of absorbed substances on the adsorption ability were investigated. The adsorption isotherms and adsorption kinetics of chromium (VI) ion and MB by YPS particles were also determined. The obtained results confirmed that the green technology used to treat the YPS2 particles is suitable to obtain an effective absorbent. The adsorption efficiency of YPS2 particles for removal of chromium (VI) ions is smaller than that for removal of MB in aqueous solutions. The adsorption isotherm of MB adsorption process is complied with the Langmuir isotherm while the adsorption kinetic fits well with the pseudo-second-order reaction model. The thermodynamic parameters of MB adsorption processed on YPS2 were calculated and discussed.